International Distribution Channels in Dental Equipment Industry: Exclusive Distributord Versus Non Exclusive Distributors (REGE Revista de Gestão, 2013)
The purpose of this study is to analyze, in a comparative way, the strategies of international channels used by a Brazilian company (ALFA) and a foreign one (BETA) of the same industry – dental equipment –, discussing elements of the relation between producers and their intermediate with respect to the exclusivity or not of the intermediate in representing those brands. The method used was the multi case study. We can highlight the following results: (a) operate with independent international distributors is a way of exporting with broad geographic scope and low investment; it was a way of accelerating the internationalization of the production company; (b) the selection of distributors accepting contractual terms that give the manufacturer more control over marketing key variables, especially those related to positioning and brand image, depends on the desired position, or already conquered, by the distributor; (c) the strategy of direct investment abroad is the result of the market vision sometimes much larger than the one of their country of origin; (d) technology products with high impact on client’s work have the consequence of making the clients establish close relationship with the distributor, buying several other items necessary to a dental office; (e) the issue of exclusivity has more shades than it seems. There are models in which power in manufacturer-distributor dyad weighs over to one side. In new markets, the distributor seems to have more power, since it is who has the key to the foreign market.